Ethnic Violence Against Japanese Migrants In California - Syawali, Noorasani; Ong, Susy; Rustam, Muhammad Reza (MSJ : Majority Science Journal, 2024)
This article discussed the persistence of ethnic conflicts around the world, evolving from post-World War II national disputes to internal conflicts driven by ethnic and intergroup tensions. These problems impeded democratization and remained crucial to the development of societies and national identities. Ethnic violence was an example of political violence rooted in ethnic hatred. Countries such as the United States, with its racially and ethnically diverse population, faced significant challenges of ethnic discrimination against Japanese immigrants. Japanese immigration to the United States, especially in California, which began in the mid-1880s, was driven by labor shortages following the Chinese Exclusion Act of 1882 and later by economic difficulties in Japan. United States immigration policies, especially the Acts of 1917 and 1924, imposed restrictions on Asian immigrants, which impacted Japanese immigration. This study, using qualitative research with a descriptive overview through the densho.org portal, aimed to analyze Japanese ethnic violence in California. Racism and economic competition fueled anti-Japanese violence. Anti-Japanese sentiment increased, especially after the attack on Pearl Harbor, which led to the mass internment of Japan-American.